PERLINDUNGAN HUKUM TERHADAP HAK ANAK DALAM PERKAWINAN DAN PEMBAGIAN WARISAN DI INDONESIA - Pradipta Mulya Pratama; Fitria Agustin (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Children are vulnerable legal subjects in the dynamics of family law in Indonesia. This article analyzes legal protection of children's rights, particularly in marriage (including early and unregistered marriages) and the status of children in inheritance distribution according to positive law and Islamic law. Using normative juridical research methods, this study concludes that although regulations such as the Child Protection Law and the Marriage Law have provided a basic framework, their implementation still faces obstacles in synchronizing regulations, particularly regarding the status of illegitimate children and the inheritance rights of children from unregistered marriages.